Photoelectrocatalytic Electrodes with High Activity for Methylene Blue Degradation - Meng, Ze-Da; Zhu, Lei; Ullah, Kefayat; Ye, Shu; Park, Chong-Yeon; Oh, Won-Chun (Asian Journal of Chemistry, 2013)
In this study, a series of electrodes were prepared. The decrease of surface area compared with that of the pristine AC indicated the blocking of micropores on the surface of the activated carbons; was further supported by SEM, XRD, EDX. It was found that catalytic decomposition of methylene blue solution could be attributed to synthetic effects between the TiO2 photocatalysis and electro-assisted activated carbons network and that photoelectrocatalytic oxidation increased with added of Co and graphene composition.